The differentiation of HL-60 cells in the synthetic medium induced by GM3 ganglioside. Issue 6 (June 1985) - Senoo, Haruki; Momoi, Takashi
Abstract : GM3 ganglioside, added exogenously to a promyelocytic leukemia cell line (HL-60 cells) in serum-free synthetic medium, induced differentiation into macrophage-like cells. Macrophagic morphology and function of differentiation-induced cells were determined by cell growth behavior, May-GriJnwald-Giemsa staining, activities of nonspecific esterase, phagocytosis and nitroblue tetrazolium (NBT) reduction. GM3 ganglioside may play a role in triggering differentiation of HL-60 cells into macrophage-like cells.